Danças circulares sagradas: a contribuição de Bernhard, Maria Gabriele Wosien e a imagem do corpo-dançante a sobrevivência das danças circulares - Moya, Leisi Fernanda (2019)
Dance is an anachronistic artistic and cultural manifestation, because it crosses all the historical times of humanity, since the earliest times. Its survival is due to its adaptability and to always being reinvented front to all the social transformations which the human existence is subject. Since dance can be analyzed by different approaches, it is proposed a clipping and focus in the Sacred Circle Dance (SCD). The SCD arose at the end of the 20th century, but its matrix carries traces and characteristics that bring it closer to millennial dances, such as traditional dances or folk dance. Thus, we sought to investigate the survival and how the process of appropriation and re-signification of the traditional folk dance for the creation of SCD, theory/pedagogy idealized by Bernhard and his daughter Maria Gabriele Wosien. The purpose of this study was to investigate: "What is the role of DCS in the survival and resignification of the wheel dance and in what way the image of the dancing body can act as devices of memory and tradition?" With this aim, an incursion was made in bibliographical references and in imagery records that refer us to dance, especially to circle and traditional dances. Based on the assumption of Aby Warburg that the images are great sources and transmitters of memory, they were highlighted and, together with the textual records, contributed in the elaboration of a historiography and small atlas of images of circle dance. The readings and analysis of the images enabled the realization that the circle dance is one of the oldest manifestations created by the human being. The imaging records of the dancing body allowed to visualize a trail of history, memories and traditions linked to the sacred and pagan rituals of our ancestors. These records led us through the historical tracks of circle dance, revealing a continuous, even if oscillating, presence throughout our historical trajectory. We conclude that the dance body is a living instrument of memory, through the choreographed gestures, passed on into the groups, and of the image registers, traces of our cultural history survived time and the unstoppable social changes. In the same way, we infered that the seek for the sacred or for something that transcends is very strong in the human being and the dance, in one way or another, has always been linked to this search.